Simulacra and virtualization technologies in information society - Vadim A. Emelin (Национальный психологический журнал, 2016)
In this paper virtualization and simulation technologies in the context of higher mental functions in information society are observed. The category of “simulacrum” considered within the representative model (Plato) and unrepresentative model (Deleuze, Baudrillard) is considered as a key factor for the theoretical analysis of virtual reality. Virtual reality is described as a space of simulacra, special signs that, unlike signs-copies do not fix any similarity, but fix dissimilarity with reference reality generating a sequence of simulations. A problem of subjectivity is highlighted, containing the merger of the subject and simulacrum in virtual reality. Thus, staying in a real world physically, the subject transits into a virtual world mentally. There it is endowed by a new virtual body, that has nothing in common with the subject’s corporeality. There are traps for technological simulacra related to the development of phantom reality and to the possibilities of combining virtual and true reality. Nowadays, technologies are becoming such power that is capable if erasing the border between a signifier and the signified. “Virtual” events play the leading role in information space. However, they generate real consequences, again acquiring real reflections and making an endless chain of switches between the real and the virtual events. As an example of destructive simulation, the use of virtual technologies for conducting military actions or for creating and promoting news events in mass media is given. It is stated that have become an inseparable part of cultural and historical reality of information society. It is indistinguishability of virtual and real entity that is defined as a reason of transformational processes of not only the identity but also of higher mental functions.